2020
DOI: 10.2166/wrd.2020.040
|View full text |Cite
|
Sign up to set email alerts
|

Reuse of municipal wastewater for different purposes based on a modular treatment concept

Abstract: Due to water scarcity and water pollution, the importance of water reuse is increasing more and more. As part of a German research programme on water reuse, the effluent of a wastewater treatment plant in the coastal region of northern Germany was used to investigate the direct treatment of tertiary effluent within the project MULTI-ReUse. A modular constructed pilot system has been operated to optimize different treatment chains producing different water qualities simultaneously. The technological focus was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The success of the pore preparation process in multi-layer graphene membrane derives from the ability of CS to form conformal, continuous films on arbitrary substrates and its subsequent transformation into defective doped G upon pyrolysis at 600 • C. Pyrolysis causes a profound structural change of the polysaccharide forming doped G even after physical treatment. The goal was to achieve a membrane able to reject CECs and allow the permeation of nutrients, producing a safe and nutrient-rich permeate for irrigation in agriculture [58]. For example, recent experimental investigations using a microfiltration membrane proved that physical opening methods using an electron beam or a laser could be an excellent approach to create variable-sized graphene nanopores to tune selectivity and molecular diffusivity [59].…”
Section: Pmr Tests Using Synthetic Cecs Solutionsmentioning
confidence: 99%
“…The success of the pore preparation process in multi-layer graphene membrane derives from the ability of CS to form conformal, continuous films on arbitrary substrates and its subsequent transformation into defective doped G upon pyrolysis at 600 • C. Pyrolysis causes a profound structural change of the polysaccharide forming doped G even after physical treatment. The goal was to achieve a membrane able to reject CECs and allow the permeation of nutrients, producing a safe and nutrient-rich permeate for irrigation in agriculture [58]. For example, recent experimental investigations using a microfiltration membrane proved that physical opening methods using an electron beam or a laser could be an excellent approach to create variable-sized graphene nanopores to tune selectivity and molecular diffusivity [59].…”
Section: Pmr Tests Using Synthetic Cecs Solutionsmentioning
confidence: 99%
“…It was found that polymeric materials (e.g., PE pipes) are suitable for all three types of ReUse Water. Due to the high neutral salt concentration of ReUse Waters 1 and 2, metallic items can only be used under specific network construction and service circumstances, and corrosion inhibitors may be required [104].…”
Section: Germany: Multi-reuse Projectmentioning
confidence: 99%
“…A vital issue to consider when reusing wastewater is the water quality required to address specific consumers' needs. Different levels of treatment are required to supply the quality of water demanded by different consumers [21]. The desired quality of water is addressed by using different technological processes to purify the water.…”
Section: Literature Reviewmentioning
confidence: 99%